Two Novel CYP11B1 Gene Mutations in Patients from Two Croatian Families with 11β-Hydroxylase Deficiency - Katja Dumic; Tony Yuen; Zorana Grubic; Vesna Kusec; Ingeborg Barisic; Maria I. New (International Journal of Endocrinology)
Steroid 11β-hydroxylase deficiency (11β-OHD) is the second most common cause of congenital adrenal hyperplasia. Mutations in the CYP11B1 gene, which encodes steroid 11β-hydroxylase, are responsible for this autosomal recessive disorder. Here, we describe the molecular genetics of two previously reported male siblings in whom diagnosis of 11β-OHD has been established based on their hormonal profiles displaying high levels of 11-deoxycortisol and hyperandrogenism. Both patients are compound heterozygous for a novel p.E67fs (c.199delG) mutation in exon 1 and a p.R448H (c.1343G>A) mutation in exon 8. We also report the biochemical and molecular genetics data of one new 11β-OHD patient. Sequencing of the CYP11B1 gene reveals that this patient is compound heterozygous for a novel, previously undescribed p.R141Q (c.422G>A) mutation in exon 3 and a p.T318R (c.953C>G) mutation in exon 5. All three patients are of Croatian (Slavic) origin and there is no self-reported consanguinity in these two families. Results of our investigation confirm that most of the CYP11B1 mutations are private. In order to elucidate the molecular basis for 11β-OHD in the Croatian/Slavic population, it is imperative to perform CYP11B1 genetic analysis in more patients from this region, since so far only four patients from three unrelated Croatian families have been analyzed.